2008
DOI: 10.1097/pep.0b013e318172432d
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Muscle Strength in 6- to 8-Year-Old Children Using Hand-Held Dynamometry

Abstract: This study provides hand-held dynamometer strength reference values to enable clinicians to determine if clients of the same age, height, and weight have muscle weakness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 25 publications
2
49
1
3
Order By: Relevance
“…Preliminary analysis showed that our study sample was generally similar in height, weight [18,20,33], and BMI [19,38] compared with other studies, but boys and girls of our study sample were slightly taller and had higher body weight from 13 years onwards. The results of the muscle strength measurements were comparable with previous studies [2,4,11,18,20,24,31], but our results showed, in most cases, a somewhat lower muscle strength, especially after puberty. This might be caused by the different measurement methods.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Preliminary analysis showed that our study sample was generally similar in height, weight [18,20,33], and BMI [19,38] compared with other studies, but boys and girls of our study sample were slightly taller and had higher body weight from 13 years onwards. The results of the muscle strength measurements were comparable with previous studies [2,4,11,18,20,24,31], but our results showed, in most cases, a somewhat lower muscle strength, especially after puberty. This might be caused by the different measurement methods.…”
Section: Discussionsupporting
confidence: 93%
“…Although several studies are published establishing normative data for muscle strength in children [4,18,24], adolescents, and young adults for different muscle groups, only in a few studies anthropometrical variables were specified [2,11,20,31,41]. Reliable muscle strength measurement of different muscle groups is time-consuming and a quick and simple measurement might provide a good indication of the general muscle strength.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies report body mass as the strongest correlate with muscle strength in children, [8][9][10][11] while others demonstrate as we did that height showed the strongest relationship and was the most significant predictor of strength. 23,24 In adults, a decline in strength was most strongly associated with aging in 5 muscle groups (hand grip, ankle dorsiflexors, shoulder external rotators, knee flexors, and extensors), while in older adulthood all muscle groups demonstrated a significant decline in strength associated with aging. These results suggest a musclespecific response to aging during adulthood and that generalized weakness does not occur until older adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…A study achieved with children found that those with higher age, height and weight (alone or in combination) showed higher strength in six muscle groups of the lower limbs, and the height was the strongest predictor of the strength compared to the age or weight (23) . However there is no research on the influence of body height in the tongue force.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of weight, height and body mass index (BMI) on tongue strength has been little studied. Most research on the height and weight as determinants of muscle strength study the muscles of other parts of the body and not specifically the tongue ones (23) . Some studies have considered these aspects to basically perform the match between the surveyed groups, assuming therefore to be the responsible parameters for differences between groups (24,25) .…”
Section: Introductionmentioning
confidence: 99%